Notes on the nest of the social wasp Pseudopolybia langi (Hym., Vespidae, Polistinae) - Sherlem Patricia de Seixas Felizardo; Ian Patrick Vilhena dos Santos; Orlando Tobias Silveira (Revista Brasileira de Entomologia, 2018)
Detailed descriptions of the architecture of Pseudopolybia langi nests are presented for the first time. Structural variations in the arrangements of nest parts are described and compared with features observed in other species of Pseudopolybia and other epiponine genera. Keywords: Nest architecture, Social behavior, Epiponini, Neotropical, Amazonia